The Concept of State Defense in the Millennial Era and in the midst of the Pandemic Covid -19 According to the Foundation of State Defense in Article 27 Paragraph (3) and Article 30 Paragraph (1) of UUD 1945 (by PPWK activities National Insight Education - Ragil Ira Mayasari (Faculty of Law, Merdeka University Surabaya, 2020)
Based on Article 27 Paragraph (3) and Article 30 Paragraph (1) of UUD 1945 in increasing the sense of State Defense, Bakesbangpol Mojokerto City plays an active role among high school students in Mojokerto City with the PPWK activity